Bone Marrow-Derived Mononuclear Cell Transplantation Can Reduce Systemic Inflammation and Endothelial Glycocalyx Damage in Sepsis. Issue 2 (August 2021) - Matsubara, Tsunehiro; Umemura, Yutaka; Ogura, Hiroshi; Matsuura, Hiroshi; Ebihara, Takeshi; Matsumoto, Hisatake; Yamakawa, Kazuma; Shimizu, Kentarou; Okada, Hideshi; Shimazu, Takeshi
Abstract : ABSTRACT: Bone marrow-derived mononuclear cells (BMMNCs) secrete anti-inflammatory mediators that protect against acute inflammation. Current evidence suggests that BMMNC transplantation can reduce acute tissue injury caused by systemic inflammation and lung dysfunction. This study evaluated the role of BMMNCs in reducing systemic inflammatory responses to vascular endothelial injury in sepsis. Bone marrow cells were harvested from the tibias and femurs of 12-week-old male Wistar rats; BMMNCs were separated by density centrifugation. Additional rats underwent cecal ligation and puncture (CLP) or similar sham surgery. BMMNCs were injected intravenously 30 min after CLP. The Sham and CLP Control groups were administered PBS. The 7-day survival rate improved markedly in the CLP-BMMNC group compared with that in the Control group. BMMNCs markedly suppressed the serum levels of pro-inflammatory mediators such as tumor necrosis factor-alpha, interleukin-6, and histone H3 at 3, 6, and 12 h after CLP. In the CLP-BMMNC group, the serum levels of syndecan-1, the main component of the vascular endothelial glycocalyx layer, were notably lower than those in the Control group 6 h after CLP. Histological analysis revealed improvement of morphological damages in the CLP-BMMNC group. Ultrastructural analysis revealed that the glycocalyx structure was maintained and the continuity of the vascular endothelial glycocalyx layer was preserved in the BMMNC group, compared with the case for the Control group at 6 and 12 h. Therefore, BMMNC transplantation may provide reduced systemic inflammation and endothelial glycocalyx damage, dramatically improving the survival of rats. These findings provide insights into formulating potential therapeutic strategies against sepsis.